Evaluation of the combined assessment of two digital enhancement filters in periapical radiographs obtained with different projection angles in the detection of simulated dental root fractures - Wanderley, Victor Aquino; Oliveira, Matheus L.; Silva, Ana Lidia Pinheiro [UNESP]; Tosoni, Guilherme Monteiro [UNESP] (Springer Nature, 2022)
Objective: To evaluate the diagnostic efficacy of the combined assessment of the original radiographic image with the Invert or Emboss digital enhancement filters in periapical radiographs obtained with different horizontal projection angles in the detection of simulated dental root fracture. Materials and methods: Thirty-four single-rooted teeth were selected, out of which 17 teeth were subjected to root fracture. Each tooth was individually placed in an empty socket of a dry human maxilla or mandible and X-rayed following the paralleling technique at three horizontal projections: mesial, right angle, distal. Then, the Invert and Emboss enhancement filters were applied. Five examiners independently evaluated all the images and rated the fractures using a 5-point scale. Weighted kappa test assessed the intra- and interexaminer agreements. Diagnostic values were calculated and the areas under the receiver operating characteristic curve (AUC) were compared using two-way ANOVA with Tukey test as post hoc (α = 0.05). Results: The inter- and intraexaminer agreement ranged from moderate to almost perfect and from substantial to almost perfect, respectively. Diagnostic values were considerably high for all conditions with no significant difference between the AUC values (p > 0.05). Conclusions: The combined use of the original radiographic image with the Invert or Emboss digital enhancement filters in periapical radiographs obtained with different projection angles did not influence the detection of simulated dental root fracture.
Keywords: Dental digital radiography; Diagnostic imaging; Radiographic image enhancement; Tooth fractures